Gluten-free, casein-free diet for children with autism spectrum disorder: A case-controlled study - Khaled Saad; Islam Shabaan; Abd-; Mohamed Ezzat; Mohamed A Abouzed; Yasser Hamed; Mohamed Fahmy M. Ibrahim; Eman F Gad (Wolters Kluwer Medknow Publications, 2024)
Background and Objectives: Numerous therapeutic and dietary interventions have been examined in the last thirty years for pediatric patients diagnosed with autism spectrum disorder (ASD). Our interventional study aimed to assess the effectiveness of the gluten-free, casein-free (GFCF) diet in a cohort of Egyptian children with ASD. Materials and Methods: The present clinical trial was conducted as a prospective 12-month, open-label, case-controlled interventional study. Thirty-six ASD children who were newly diagnosed and had not taken any prior psychiatric or rehabilitation therapy were included in this study. The patients were randomly assigned into two groups: group A, which received the GFCF diet, and group B, which served as the control group and was not restricted to food containing gluten and casein for 12 months. All patients were followed up for 1 year. Results: Following the implementation of the GFCF diet in group A, significant improvements in CARS scores were observed compared to group B after 6-month and 1-year follow-up periods. Conclusions: The introduction of the GFCF diet could be helpful and promising for autistic children. Conclusive evidence regarding the effectiveness of the GFCF diet remains a subject of controversy. Nonetheless, our study contributes some evidence supporting its potential benefits for children with ASD. It is recommended that future research on the GFCF diet employ a more sophisticated research design, incorporating a consistent baseline measure that can effectively assess the therapeutic effects of these interventions for individuals with ASD.